Patient Views on Advance Care Planning in Cirrhosis: A Qualitative Analysis - Michelle Carbonneau; Tracy Davyduke; Jude Spiers; Amanda Brisebois; Kathleen Ismond; Puneeta Tandon (Canadian Journal of Gastroenterology and Hepatology)
Aim. To investigate patient experiences and perceptions of advance care planning (ACP) process in cirrhosis. Methods. Purposive sampling was used to identify and recruit participants (N = 17) from discrete patient groups: compensated with no prior decompensation, decompensated and not yet listed for transplant, transplant wait listed, medical contraindications for transplant, and low socioeconomic status. Review and discussion of local ACP videos, documents, and experiences with ACP occurred in two individual interviews and four focus groups. Data were analyzed using inductive content analysis including iterative processes of open coding, categorization, and abstraction. Results. Three overarching categories emerged: (1) lack of understanding about disease trajectories and ACP processes, (2) roles of alternate decision makers, and (3) preferences for receiving ACP information. Most patients desired advanced care-planning conversations before the onset of decompensation (specifically hepatic encephalopathy) with a care provider with whom they had a trusting, preexisting relationship. Involvement of the alternate decision makers was of critical importance to participants, as was the use of direct, easy to understand patient education tools that address practical issues. Conclusion. Our findings support the need for early advance care planning in the outpatient setting. Outpatient clinicians may play a key role in facilitating these discussions.